2000
DOI: 10.1063/1.1332821
|View full text |Cite
|
Sign up to set email alerts
|

Photonic-crystal-based beam splitters

Abstract: We proposed and demonstrated two different methods to split electromagnetic waves in three-dimensional photonic crystals. By measuring transmission spectra, it was shown that the guided mode in a coupled-cavity waveguide can be splitted into the coupled-cavity or planar waveguide channels without radiation losses. The flow of electromagnetic waves through output waveguide ports can also be controlled by introducing extra defects into the crystals. Our results may have an important role in the design of efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(72 citation statements)
references
References 26 publications
0
71
0
1
Order By: Relevance
“…[5][6][7][8][9] Such localized modes have a potential to be used as a high Q resonator [10][11][12][13][14][15] for various frequency ranges from the microwave range up to optical frequencies. A linearly extended defect can guide waves with high efficiency, thus allowing for the construction of beam splitters, 16,17 sharp bend waveguides, 18 -22 and coupling structures. [23][24][25] Photonic crystals that are periodic in two dimensions only ͑2D photonic crystals͒ can provide a band gap for every direction of propagation in the lattice plane of periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Such localized modes have a potential to be used as a high Q resonator [10][11][12][13][14][15] for various frequency ranges from the microwave range up to optical frequencies. A linearly extended defect can guide waves with high efficiency, thus allowing for the construction of beam splitters, 16,17 sharp bend waveguides, 18 -22 and coupling structures. [23][24][25] Photonic crystals that are periodic in two dimensions only ͑2D photonic crystals͒ can provide a band gap for every direction of propagation in the lattice plane of periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…As a variation of bends, structures that can split the path of light were also investigated [97,114].…”
Section: Photonic Crystals As Devices and Applicationsmentioning
confidence: 99%
“…30 Yariv et al reformulated the same phenomenon in a simple way, and proposed various applications based on coupled-cavity structures. 33 Later, the mode splitting phenomena within the TB picture, 34 guiding and bending of EM wave, 10 heavy photons, 35 and EMbeam splitting and switching effect 47 were experimentally demonstrated in our group in three-dimensional photonic crystals at microwave frequencies. Very recently, Lan et al numerically proposed a switching mechanism by changing the positions of the sharp edges of the coupled-cavity band of 1D PBG structures 36 and delay lines for ultra short optical pulses 37 , and Olivier et al reported 2D CCWs at optical wavelengths.…”
Section: Localized Coupled-cavity Modes and The Tight Binding Approximentioning
confidence: 99%